Evaluation and subsequent minimization of matrix effects caused by phospholipids in LC–MS analysis of biological samples. (September 2013) - Janusch, Franziska; Kalthoff, Lena; Hamscher, Gerd; Mohring, Siegrun AI
Background: The influence of matrix effects in LC–MS/MS analysis of biological samples can be enormous and has to be evaluated during method development. Phospholipids, which are present in considerable quantities in biological fluids, are supposed to cause matrix effects when co-eluting with analytes. Therefore, the reduction of phospholipids should lead to the minimization of matrix effects.Methodology & Results: Here, a polymeric reversed-phase (PRP) SPE cartridge was compared with a combination of mixed-mode-anion-exchange (MAX) and mixed-mode-cation-exchange (MCX) SPE cartridges regarding elimination of matrix effects during sample clean-up. For evaluation of matrix effects post-column infusion experiments were performed. Phospholipid amount in the sample extract and matrix effects are enhanced using PRP in contrast to the combination of MAX/MCX.Conclusion: For an efficient elimination of phospholipids during sample preparation and to improve method accuracy and precision it is advisable to use a combination of MAX/MCX SPE cartridges.